Consistent modelling of hierarchical BPMN collaborations. Issue 2 (11th March 2022) - Corradini, Flavio; Polini, Andrea; Re, Barbara; Rossi, Lorenzo; Tiezzi, Francesco
Abstract : Purpose: This paper aims at supporting business process designers in modelling collaborative scenarios in terms of hierarchical BPMN collaboration diagrams, to enforce consistency among different hierarchical levels. Design/methodology/approach: The proposed approach is based on a set of guidelines to apply during the modelling of hierarchical diagrams. These guidelines address consistency issues related to the hiding capability provided by sub-process and call activity elements, which may obscure behaviours at inner levels, especially exchange of messages, that are inconsistent with those in other hierarchical levels. A laboratory experience validates the guidelines' effectiveness. Findings: The paper points out the issues of hierarchical diagrams, and the lack of support in this context from the existing BPMN modelling tools. Moreover, through a laboratory experience, the paper shows the benefits carried by the proposed guidelines concerning the quality of the modelled diagrams. Practical implications: The proposed guidelines have been implemented in a consistency checking tool that avoids consistency errors during the modelling activity. To foster its usage, the tool has been integrated into the Eclipse BPMN modelling environment. Originality/value: The paper, employing consistency guidelines, provides a novel solution to the weaknesses of hierarchical modelling.